Kompetensi Pedagogik Guru PAUD di TK Al-Manar - Alamanda, Adila Nafisa; Amanda, Cindy; Moniken, Leoni; Kurnia, Rita; Yanti, Asfi (Early Childhood Research Journal (ECRJ), 2025)
Early Childhood Education (PAUD) plays a crucial role in building the foundation of children's development. However, its implementation in Indonesia still faces obstacles related to teacher qualifications and abilities. This study aims to describe the competency profile of PAUD teachers, covering pedagogical, professional, social, and personality aspects during learning activities at Al-Manar Kindergarten. This study employed a qualitative method with a case study approach, using data collection techniques through observation, interviews, and documentation. The results indicate that teachers have not fully met the competency standards stipulated in the Minister of Education and Culture Regulation Number 137 of 2014. From a pedagogical perspective, the learning process still feels monotonous and has not adopted the principle of learning through play. From a professional perspective, mastery of material and use of learning aids are still limited. Social competence is adequate, but has not yet implemented an inclusive learning approach. In terms of personality, teachers display good ethics, but emotional control needs to be improved. In general, teacher abilities do not fully support optimal learning for early childhood. Therefore, steps are needed to improve teacher professional development and competency to improve the quality of PAUD.